The Influence of Student Teams Achievement Division combined with Discovery Learning to Improve Student Learning Outcomes and Activeness - Arief Hermanto; Agus Efendi; Nurcahya Pradana Taufik Prakisya (Pendidikan Teknik Informatika dan Komputer, Universitas Sebelas Maret, 2020)
This research aims to find out the influence of learning outcomes as well as the activeness of students in the classroom who apply the learning model of student teams achievement division combined with discovery learning with classes that apply conventional learning models. The method used is a quantitative quasi-experimental design using pretest-posttest control. The sample used in this study was 72 students consisting of 2 classes. The sampling techniques in this study used total sampling. Data is obtained from pretest and posttest results based on indicators of student learning outcomes and activeness. The results showed differences and improved learning outcomes and student activity that implemented the student teams achievement division learning model combined with discovery learning compared to conventional learning models. This is evidenced by the results of the first hypothesis test using a t-test that confirms that the posttest result is 0.00 which means the value is less than the error level of 0.05 so it can be concluded that the two classes have a significant difference (H0 rejected). Furthermore, the results of the second hypothesis test used again to test showed a score of 0.52 in the experiment class and a score of 0.28 in the control class which meant there was an increase in learning outcomes and liveliness in the experiment and control classes.